ONLINE MEDIATION IN SPAIN AND THE NEW CHALLENGES POSED BY COVID-19 - J. Aranda Serna, Francisco (Legal Bulletin, 2021)
This article examines the impact that COVID-19 pandemic is having on mediation processes in Spain. For that purpose, the guiding principles that feed mediation are analyzed together with the problems arising from the implementation of the use of new technologies an electronic media in the online mediation area. This assesment is delimited by the Spanish legislative framework and the legal and social consequences that COVID-19 has generated during 2020.